The Recent Research Development of 177Lu Radiopharmaceuticals - YANG Yuchuan;KAN Wentao;YANG Xia;WEI Hongyuan;ZHUO Liangang;WANG Jing;LIAO Wei;ZHAO Peng;WANG Guanquan (Journal of Isotopes, 2022)
Various radionuclides emitting β-, α particles, auger electrons and conversion electrons have been applied in radiopharmaceuticals development and corresponding clinical evaluations. Among these applied radionuclides, lutetium-177 related radiopharmaceuticals have attracted tremendous interest from the scientific field. There were in total less than 20 publications throughout last century. However, there emerged nearly 1000 publications on 177Lu during the past ten years, indicating more efforts have been focus on 177Lu. This article will review the development of preclinical and clinical trials of 177Lu radiolabeled antibodies, peptides, nanoparticles as well as small molecules as therapeutical 177Lu radiopharmaceuticals dating to the recent two years. In the preclinical part, the targetting property, pharmacokinetics and biological property have been improved by drug design. In the clinical part, the reviewed radiopharmaceuticals displayed excellent safety, obvious inhibitory effect on tumor, obvious effects on prolonging the patient survival as well as improving the patients’ quality of life; qualified supplementary on the current clinical administration ways such as combined radionuclide therapy, chemo-immuno-radiotherapy, radiotheranostics and seperated administrations; supplementary on the human dosimetry data such as first-in-human dosimetry of gastrin-releasing peptide receptor antagonist ［177Lu］Lu-RM2.